On the Shoulders of Giants - Eco, Umberto; Translated by Alastair McEwen (London Harvill Secker, 2019)
"On the Shoulders of Giants collects previously unpublished essays from the last fifteen years of Umberto Eco's life. With humor and erudition, one of the great contemporary thinkers takes on the roots of Western culture, the origin of language, the nature of beauty and ugliness, the imperfections of art, and the lure of mysteries"--
Include Color illustrations
Keywords: Art and society -- Art--Themes, motives -- Art--Philosophy -- Aesthetics